Engagement with Civil Society : An EITI Implementation Case Study - World Bank (Washington, DC, 2014)
Within the World Bank Group (WBG), the Oil, Gas, and Mining Policy Division (COCPO) is responsible for policy and advisory services in the oil, gas, and mining sectors, including World Bank lending. The unit also manages WBG participation in a number of donor-funded global programs and partnerships, including the Multi-Donor Trust Fund (MDTF) for the Extractive Industries Transparency Initiative (EITI). The main finding of this paper is that the direct support to civil society organization (CSO) through the Development Grant Facility (DGF) mechanism (July 2005 to June 2008) was well received and met key program objectives. In particular, DGF funding catalyzed the EITI in countries by helping strengthen CSO ability to play their role in the initiative. Working closely with the Revenue Watch Institute (RWI) during the later part of the DGF grant cycle helped COCPO build partnerships with CSO. The CSO also found the strategic nature of the DGF interventions to be positive, given that the grants allowed them to carry out a broad range of activities (advocacy, research, capacity building, and communications) around the sensitive topic of extractive industries and EITI.